An overview of oxygen vacancy dynamics in (1 − x)(Bi1/2Na1/2)TiO3–xBaTiO3 solid solution. Issue 32 (3rd August 2021) - Fan, Zhongming; Randall, Clive A.
Abstract : Across the phase diagram of (Bi1/2 Na1/2 )TiO3 -xBaTiO3 solid solution, the conduction mechanism changes from ionic to electronic through the mixed case at the morphotropic phase boundary, giving rise to distinct DC degradation behaviors. Abstract : (Bi1/2 Na1/2 )TiO3 (BNT) based ceramics have been the hot topic for a few years because of their multiple functions, from the piezoelectric properties to more recently the electrostatic energy storage performance. However, some basic issues are still unclear, preventing their wide application in real devices. One of them is the underlying conduction mechanism, the interplay of electronic and ionic carriers as a mixed ionic case and the subsequent quantification. This paper deals with the most basic compositions, which are the typical ones from the (1 − x )(Bi1/2 Na1/2 )TiO3 – x BaTiO3 (BNT– x BT) phase diagram. The conductivity is primarily investigated by impedance spectroscopy, while different equivalent circuits are applied to different conduction mechanisms. A transition from predominantly ionic to predominantly electronic conduction is revealed to occur with the increase in BaTiO3 concentration. The mixed ionic–electronic conduction in the composition near the morphotropic phase boundary, namely BNT–7%BT, is identified and then quantified. To verify our interpretation of impedance results, dc degradation is, for the first time, conducted in this family of materials, from which the electronic and ionic conductions can be easily separated by accessing the mean time to failure. The successful combination of the two methods enables us to have an overview of how the oxygen vacancy dynamics in the BNT– x BT system depends upon the phase nature or the domain structure.